2018
DOI: 10.1158/1078-0432.ccr-18-0564
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Seviteronel, a Selective CYP17 Lyase and Androgen Receptor Inhibitor, in Men with Castration-Resistant Prostate Cancer

Abstract: Seviteronel (INO-464) is a selective cytochrome P450c17a (CYP17) 17,20-lyase (lyase) and androgen receptor (AR) inhibitor with antitumor activity and This open-label phase I clinical study evaluated the safety, tolerability, pharmacokinetics and activity of once-daily seviteronel in male chemotherapy-naïve subjects with castration-resistant prostate cancer (CRPC). Seviteronel was administered at 600 mg once daily with dose titration (DT) and in modified 3 + 3 dose escalation once-daily cohorts at 600, 750, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Clinical trials for patients with ER+ or TNBC indicated that seviteronel was well-tolerated in women, with the majority of adverse events (AEs) being Grade 1/2, in addition to four Grade 3/4 AEs that may be related to seviteronel treatment 171 . Phase I trials in CRPC patients suggest that seviteronel may be an effective treatment alternative for men who are not responsive on other therapies with most reported AEs being Grade 1/2 172 . Preclinical work in AR+ TNBC demonstrates that seviteronel inhibits cell proliferation and growth on soft agar 173 .…”
Section: Second Generation Antiandrogensmentioning
confidence: 99%
“…Clinical trials for patients with ER+ or TNBC indicated that seviteronel was well-tolerated in women, with the majority of adverse events (AEs) being Grade 1/2, in addition to four Grade 3/4 AEs that may be related to seviteronel treatment 171 . Phase I trials in CRPC patients suggest that seviteronel may be an effective treatment alternative for men who are not responsive on other therapies with most reported AEs being Grade 1/2 172 . Preclinical work in AR+ TNBC demonstrates that seviteronel inhibits cell proliferation and growth on soft agar 173 .…”
Section: Second Generation Antiandrogensmentioning
confidence: 99%
“…Seviteronel has been shown to be more effective than abiraterone acetate at inhibiting CYP17 lyase (23), and seviteronel also possesses some antagonistic effects against AR, potentially rendering it a dual-AR inhibitor. In phase I studies, seviteronel has been well-tolerated both in men with castration-resistant prostate cancer (CRPC) (24) and in women with ER+ breast cancer or TNBC (25). There is hope that these novel agents, including seviteronel, will be effective in patients with AR+ cancers, including TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike abiraterone acetate, VT464, selectively inhibits the 17,20-lyase rather than 17α-hydroxylase reactions, so it is proposed that the combination with prednisone is not necessary. However, phase 1 testing of VT464 suggested that there is minor inhibition of CYP17 hydroxylase ( 52 ), so low-dose dexamethasone is being administered with VT464 in ongoing trials with prostate cancer patients ( 53 , 54 ). Abiraterone acetate and VT464 both also function as competitive AR antagonists, including of AR mutants, with VT464 more potent than abiraterone in cells with the T878A AR mutation ( 55 58 ).…”
Section: New Strategies For Directly Targeting the Ar In Crpcmentioning
confidence: 99%